Long COVID brain fog and muscle pain are associated with longer time to clearance of SARS-CoV-2 RNA from the upper respiratory tract during acute infection - Antar, Annukka A. R.; Yu, Tong; Demko, Zoe O; Hu, Chen; Tornheim, Jeffrey A.; Blair, Paul W.; Thomas, David L.; Manabe, Yukari C. (Frontiers in Immunology, 2023)
The incidence of long COVID is substantial, even in people who did not require hospitalization for acute COVID-19. The pathobiological mechanisms of long COVID and the role of early viral kinetics in its development are largely unknown. Seventy-three non-hospitalized adult participants were enrolled within approximately 48 hours of their first positive SARS-CoV-2 RT-PCR test, and mid-turbinate nasal and saliva samples were collected up to 9 times within the first 45 days after enrollment. Samples were assayed for SARS-CoV-2 using RT-PCR and additional test results were abstracted from the clinical record. Each participant indicated the presence and severity of 49 long-COVID symptoms at 1-, 3-, 6-, 12-, and 18-months post-COVID-19 diagnosis. Time from acute COVID-19 illness onset to SARS-CoV-2 RNA clearance greater or less than 28 days was tested for association with the presence or absence of each of 49 long COVID symptoms at 90+ days from acute COVID-19 symptom onset. Brain fog and muscle pain at 90+ days after acute COVID-19 onset were negatively associated with viral RNA clearance within 28 days of acute COVID-19 onset with adjustment for age, sex, BMI ≥ 25, and COVID vaccination status prior to COVID-19 (brain fog: aRR 0.46, 95% CI 0.22-0.95; muscle pain: aRR 0.28, 95% CI 0.08-0.94). This work indicates that at least two long COVID symptoms - brain fog and muscle pain – at 90+ days from acute COVID-19 onset are specifically associated with longer time to clearance of SARS-CoV-2 RNA from the upper respiratory tract.